2013
DOI: 10.11648/j.sd.20130101.11
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Coupling Effects of Waves in A Panda Ring

Abstract: All forms of waves in circular motions in circular ring resonator have shown the interesting behaviors, especially, in the nonlinear wave tracks, where the waves such as gravitation wave, sound wave, electromagnetic wave, matter wave and water wave can produce the whispering gallery modes (WGMs) with some certain conditions. This paper presents the use of a circular resonator (ring resonator) which is coupled by two nonlinear side rings known as a PANDA ring, in which the input waves can be in the forms of sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…The use of THz technology can be adopted to employ with human tissue penetration and investigation, where there are many research reported for imaging and investigations [10,11]. The interesting result of whispering gallery mode (WGM) of light within a tiny optical device to generate the 3D image basic device known as a conjugate mirror can be easily constructed by using the WGMs of light within a PANDA ring circuit [12,13]. The WGMs with THz frequency range can be generated and used to form the 3D image and linked to the optic nerves in human brain [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of THz technology can be adopted to employ with human tissue penetration and investigation, where there are many research reported for imaging and investigations [10,11]. The interesting result of whispering gallery mode (WGM) of light within a tiny optical device to generate the 3D image basic device known as a conjugate mirror can be easily constructed by using the WGMs of light within a PANDA ring circuit [12,13]. The WGMs with THz frequency range can be generated and used to form the 3D image and linked to the optic nerves in human brain [14].…”
Section: Introductionmentioning
confidence: 99%
“…THz radiation consists of electromagnetic waves with frequency between 0.1 THz to 10 THz, and is widespread biomedical application involving the interaction of terahertz pulse with biological media [31][32][33][34][35][36], where THz radiation has been used successfully as a noninvasive imaging technique for detection of human skin cancer [37,38]. Recently, Yupapin et al have shown the interesting results of whispering gallery mode of light within a PANDA ring circuit [13,14], in which the advantage is that the WGMs can be easily generated and controlled within the PANDA ring circuit, which can be useful for various applications. The other applications of Panda ring resonator can be found in references [39][40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…However, searching of new techniques remain. Recently, Yupapin has reported an interesting technique of light behaviors that use whispering gallery modes (WGMs) of light in a PANDA ring, 13 which can be easily applied for nerve/cells communications, 14 i.e., remote monitoring, where the use of microscale device based on microring resonator circuits has shown promising challenges. By using this proposed technique, mobile communication link of the psychiatric investigation can be formed via the radio frequency generated by the microring circuits, which will be detailed in the following paragraph.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the center ring is coated with Au or other conducting materials, e.g., Ag, Cu, etc. This particular con¯guration is known as a \PANDA" ring resonator 13,26 and is shown in Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…Till now, however, we still search for the new techniques that can show the advantage over the past components. Recently, Yupapin [5] have proposed the very interesting technique that uses WGMs in a PANDA ring waveguide for many applications [6,7].…”
Section: Introductionmentioning
confidence: 99%